Analytical study of the new Saudi universities system issued by Royal Decree No. (M/ 27) dated 3/2/1441 AH، and the extent of its harmony with the Kingdom’s Vision 2030 - Al-Warthan, Adnan Ahmad (Journal of Educational and Psychological Sciences, 2021)
The study aimed to find out the extent to which the new system of universities was consistent with the vision of the Kingdom 2030، and the study used the descriptive، analytical، deductive، and documentary approach. The tool represented in the analysis of documents by studying the document of the book of the new system for universities issued by Royal Decree No. (M/ 27) dated 3/2/ 1441 AH، and Ministerial Circular No. 83909/ dated 7/8/1441 AH، regarding measuring the readiness of universities to implement this new system for universities، as well as the Kingdom Vision 2030 document. The results showed that the general objectives of the Kingdom’s 2030 vision that have to do with the new system of universities in accordance with the detailed goals of the vision reached Its rate is 65% compared to the rest of the state’s sectors، and that 70% of the above 65% has achieved consistency and harmony between what was stated in the new university system and the goals of the Kingdom’s Vision 2030، This confirms that the construction of the new university system took into account the goals of Vision 2030، and achieved a true reflection of the contents of the Kingdom’s 2030 vision، and finally the results indicated that 30% of the detailed goals of the Kingdom’s 2030 vision were not included in the new university system and did not focus on them in its articles، and the detailed goals are distributed The new system of universities has been consistent with them according to the main axes of the Kingdom’s 2030 vision، as follows: A/ a vibrant society 47%، b/ a prosperous economy 13%، and c/ an ambitious nation 34% Based on the results، the researcher presented a set of recommendations to complete the mechanism of harmonization and compatibility of the new system for universities with the Kingdom’s vision 2030، and to activate it in terms of practical reality and some of these recommendations are as follows: 1- Working on completing the remaining percentage of 30% to achieve complete consistency and harmony between the new university system and the Kingdom’s 2030 vision. Among these recommendations: Work to complete the remaining 30% in order to achieve consistency and integrated harmony between the new university system and the Kingdom’s 2030 vision، through the establishment of the University Affairs Council، a representative of the Ministry of Education، to focus on the missing percentages in both the axis of "a vibrant society by 47%. An ambitious homeland by 34%، a thriving economy by 13%"، while ensuring a balance with regard to the main axes of the Kingdom’s 2030 vision.